2011
DOI: 10.1364/oe.19.002580
|View full text |Cite
|
Sign up to set email alerts
|

The creation and annihilation of optical vortices using cascade conical diffraction

Abstract: Internal conical diffraction produces a superposition of orthogonally polarised zero- and first-order Bessel like beams from an incident circularly polarised Gaussian beam. For right-circularly polarised light, the first-order beam has an optical vortex of charge -1. Upon propagation of the first-order beam through a second biaxial crystal, a process which is termed cascade conical refraction, the generated beam is a superposition of orthogonally polarised fields of charge 0 and -1 or 0 and -2. This spin to or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 21 publications
2
48
0
Order By: Relevance
“…These predictions have been shown to agree well with theory for the case of the conically diffracted Gaussian beam [9,10]. The propagation of paraxial light beams along the optic axes of successive biaxial crystals, known as cascade conical diffraction, has been receiving interest recently for the creation and annihilation of optical vortices [11], as a versatile beam shaping tool [12] and in connection with a novel type of laser based on conical diffraction [13]. Berry has provided a paraxial theory for a general N-crystal cascade in which the relative orientation of crystals of differing lengths is considered [14].…”
Section: Introductionsupporting
confidence: 52%
“…These predictions have been shown to agree well with theory for the case of the conically diffracted Gaussian beam [9,10]. The propagation of paraxial light beams along the optic axes of successive biaxial crystals, known as cascade conical diffraction, has been receiving interest recently for the creation and annihilation of optical vortices [11], as a versatile beam shaping tool [12] and in connection with a novel type of laser based on conical diffraction [13]. Berry has provided a paraxial theory for a general N-crystal cascade in which the relative orientation of crystals of differing lengths is considered [14].…”
Section: Introductionsupporting
confidence: 52%
“…The reported results can be particularly interesting for experiments with tightly focused beams [101], for the generation of novel polarizations in CR [81], in optical micromanipulation [80,142,143], mode conversion between Heremite-Gauss-like beams and Laguerre-Gauss-like beams [76] and in super-resolution imaging [85]. It is also promising the generation of polarization-tunable potentials to inject, extract and ma-nipulate ultra-cold atoms [55,144].…”
Section: Discussionmentioning
confidence: 86%
“…The images show two remarkable phenomena: (i) every two diametrically opposite points at the light pattern are orthogonally polarized at any plane, and (ii) the polarization distributions of both light cones are the same. Multiple concentric rings in CR have been experimentally reported in a cascade of two [33,75,76], three [77] and up to four [78] BCs, with interesting applications in lasing [79], particle trapping [80], vortex generation [81] and free space optical communications [82]. The diffracting wave theory of CR has been extended by Berry to the case of cylindrically symmetric beams propagating through a cascade of up to N BCs [75,83], providing an accurate description of the phenomenon in terms of Bessel functions.…”
Section: Methodsmentioning
confidence: 99%
“…Two-crystal cascade conical refraction has been used in the construction of a high efficiency optically pumped laser [22]. We have studied the creation and annihilation of optical vortices in cascade conical refraction using careful manipulation of the polarization between successive biaxial crystals [23]. In a recent study, we have experimentally investigated cascade conical refraction for two crystals, of equal and unequal lengths, and shown that the results are in good agreement with the paraxial theory of conical refraction [24].…”
Section: Cascade Conical Refraction Of Lightmentioning
confidence: 80%